A novel hybrid sustainable healthcare supply chain model for patient safety: A case study of Cambodia - Kanokphanvanich, Chayada; Rattanawong, Wanchai; Vongmanee, Varin (International Journal of Innovative Research and Scientific Studies, 2024)
This research focuses on elucidating the attributes of a Sustainable Healthcare Supply Chain (SHSC) that play a pivotal role in enhancing patient safety, particularly in developing nations. Patient safety in healthcare supply chains is paramount, particularly in the face of inherent risks and vulnerabilities associated with disruptions and uncertainties. A hybrid selection model, integrating factor analysis, structural equation modeling (SEM), and the Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), is introduced to rank these attributes. Twenty-two SHSC attributes are categorized into four facets: social, environmental, economic, and technological. A survey conducted across five Cambodian provinces gathered 361 valid responses from healthcare professionals, forming the basis for a structural SHSC model. This model is subsequently implemented in a Phnom Penh tertiary hospital. The findings underscore the imperative of incorporating patient safety considerations into healthcare supply chains. The hybrid selection model helps healthcare leaders figure out what factors are most important for patient safety and rank them. This gives them information they need to come up with effective strategies and long-lasting projects. The study’s outcomes provide actionable insights for healthcare stakeholders. The multi-analytical approach of the model offers a comprehensive perspective to address supply chain challenges, reduce extraneous costs, and minimize environmental footprints. In essence, the effective implementation of sustainable healthcare supply chain strategies not only enhances care quality and fortifies patient safety but also aligns with the broader objectives of healthcare entities.